2023
DOI: 10.7554/elife.83618
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of skeletal muscles from wild-type and transgenic mice carrying recessive Ryr1 mutations linked to congenital myopathies

Abstract: Skeletal muscles are a highly structured tissue responsible for movement and metabolic regulation, which can be broadly subdivided into fast and slow twitch muscles with each type expressing common as well as specific sets of proteins. Congenital myopathies are a group of muscle diseases leading to a weak muscle phenotype caused by mutations in a number of genes including RYR1. Patients carrying recessive RYR1 mutations usually present from birth and are generally more severely affected, showing preferential i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…We next assessed the in situ muscle contraction and relaxation properties on anesthetized animals through electrical stimulation of the fast-twitch tibialis anterior (TA) muscle. A previous report found higher Orai1 expression levels in fast-twitch type II than in slow-twitch type I myofibers in mice ( 45 ), suggesting that the TA is an appropriate muscle to detect a potential therapeutic effect of ORAI1 inhibition on muscle function. At low stimulation frequencies between 10 and 40 Hz, the force of Stim1 R304W/+ muscles increased more rapidly compared with healthy WT and Orai1 R93W/+ controls ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 94%
“…We next assessed the in situ muscle contraction and relaxation properties on anesthetized animals through electrical stimulation of the fast-twitch tibialis anterior (TA) muscle. A previous report found higher Orai1 expression levels in fast-twitch type II than in slow-twitch type I myofibers in mice ( 45 ), suggesting that the TA is an appropriate muscle to detect a potential therapeutic effect of ORAI1 inhibition on muscle function. At low stimulation frequencies between 10 and 40 Hz, the force of Stim1 R304W/+ muscles increased more rapidly compared with healthy WT and Orai1 R93W/+ controls ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 94%
“…Although MYH1 has not been clearly associated to date with RYR1 -related myopathies, MYH1 mutations were associated with non-exertional rhabdomyolysis phenotype in horses 40 and MYH1 was recently considered a candidate gene for recurrent rhabdomyolysis also in humans 41 . Interestingly, the proteomic study of Eckhardt et al 42 showed a quantitative reduction of MYH1 in a mouse model with biallelic RYR1 mutations; accordingly, Wang et al 43 showed a significant reduction of MYH1 expression in muscle tissue from RYR1 mutated patients and suggested MYH1 as potential biomarkers for RYR1- myopathies. These data, together with the found interaction with CCDC78, reinforce the hypothesis of an intimate role of MYH1 with other SR proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, although morphometric studies are not available for EO muscles, it was reported that the SR is variably developed in different rat EO muscle fibres (Pachter, 1983). Surprisingly, quantitative proteomic analyses at the whole muscle level have shown that most SR proteins, except STIM1, are less abundant in mouse EO than in limb fast muscles (Eckhardt et al., 2023). However, proteomics analyses at the single fibre level are not available.…”
Section: Introductionmentioning
confidence: 99%